1992
DOI: 10.3109/00365599209181222
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral Prostatectomy Compared with Incision of the Prostate in the Treatment of Prostatism Caused by Small Benign Prostate Glands

Abstract: In a prospective, randomized study 60 patients with prostatism caused by small prostate glands (estimated weight < 20 g) had either transurethral prostatectomy (TURP, n = 31) or transurethral incision of the prostate (TUI, n = 29). Operating time and blood loss were significantly less in the group that underwent TUI. There were no differences between the groups in number of days with an indwelling catheter or days in hospital after operation. Eight patients in the TUI group required further operation, as did f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 12 publications
1
44
0
1
Order By: Relevance
“…Despite marked differences between studies in overall length of stay, in six 135,149,152,157,182,185 they reported it to be shorter for TUIP and in two 180,183 there was no difference. Two RCTs 157,182 reported data that were suitable for synthesis.…”
Section: Length Of Hospital Staymentioning
confidence: 89%
See 3 more Smart Citations
“…Despite marked differences between studies in overall length of stay, in six 135,149,152,157,182,185 they reported it to be shorter for TUIP and in two 180,183 there was no difference. Two RCTs 157,182 reported data that were suitable for synthesis.…”
Section: Length Of Hospital Staymentioning
confidence: 89%
“…152,157,180,182,183,185 There was marked heterogeneity across the studies, with no clear pattern of results (Figure 15, comparison 05:03:04: 23/263 versus 17/265, RR 1.33, 95% CI 0.77-2.31, p = 0.30). The source of heterogeneity was uncertain, although the lack of separation between urethral stricture and bladder neck contracture may have been a factor as definitions of these conditions varied across the trials.…”
Section: Stricturementioning
confidence: 99%
See 2 more Smart Citations
“…2 However, TUIP has significantly shorter operative time and hospital stay than TURP. [11][12][13][14] Nevertheless, there is little evidence on long-term effectiveness and there is no clear cutoff prostate size that achieves long-term favourable outcomes after TUIP. Prostate size was found to correlate with BOO Prostate size and long-term outcome in patients with a prostate volume ≥30 g, a finding which was not seen in patients with smaller prostates.…”
Section: Discussionmentioning
confidence: 99%